Corrosion‐Induced Strengthening: Development of High‐Strength Nanoporous Metals1 . Issue 6 (29th December 2015) - Ye, Xing‐Long; Jin, Hai‐Jun
Abstract : Replacing parts of a solid with voids usually weakens a material. Here, we report that a material (Au–Pt–Ag alloy) becomes stronger by 7 times, its strength increases from 50 to 345 MPa, when ≈40% of solids (Ag) is dissolved and replaced by pores during dealloying. The corrosion‐induced strengthening originates from the formation of nanoporous structure, and the high strength of nanoscale ligaments due to size effect. The results also suggest that the connectivity of nanoporous structure decreases during coarsening, leading to additional decreases in strength and stiffness, which may explain the unexpected low strength and stiffness of previously reported nanoporous gold. Abstract : In conventional materials, replacing parts of a solid with voids usually leads to a decrease in its strength . Here, the authors report that a material (Au–Pt–Ag alloy) can bear seven times higher load – its compressive strength increases from 50 to 345 MPa, when ≈40% of solid component (Ag) is dissolved and replaced with pore space during dealloying.